2022
DOI: 10.1021/acs.est.1c06118
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Halogenated Byproducts upon Water Treatment with Peracetic Acid

Abstract: Peracetic acid has quickly gained ground in water treatment over the last decade. Specifically, its disinfection efficacy toward a wide spectrum of microorganisms in wastewater is accompanied by the simplicity of its handling and use. Moreover, peracetic acid represents a promising option to achieve disinfection while reducing the concentration of typical chlorination byproducts in the final effluent. However, its chemical behavior is still amply debated. In this study, the reactivity of peracetic acid in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Noteworthy, only brominated THMs (CHBr 3 ) and HAAs (MBAA, DBAA, and TBAA) were detected during PAA treatment in the saline waters without NOM (Figure c, d). As far as the chlorine-containing byproducts are concerned, the kinetic data suggested that HOCl would be formed from PAA/Cl – at a rate that is 6 orders of magnitude lower than HOBr formed from PAA/Br – . Considering that HOCl reactivity in the halogenating reaction is likewise significantly lower than that of HOBr, it appears that PAA/X – process is not a reasonable source of chlorinated byproducts (Text S10).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Noteworthy, only brominated THMs (CHBr 3 ) and HAAs (MBAA, DBAA, and TBAA) were detected during PAA treatment in the saline waters without NOM (Figure c, d). As far as the chlorine-containing byproducts are concerned, the kinetic data suggested that HOCl would be formed from PAA/Cl – at a rate that is 6 orders of magnitude lower than HOBr formed from PAA/Br – . Considering that HOCl reactivity in the halogenating reaction is likewise significantly lower than that of HOBr, it appears that PAA/X – process is not a reasonable source of chlorinated byproducts (Text S10).…”
Section: Resultsmentioning
confidence: 98%
“…Among them, CHBr 3 (40.5 μg/L) was the dominant species of Br-DBPs, but only accounted for 3.5% of TOBr (Figure b). The electron-rich moieties of NOM (e.g., phenolic groups) can offer more active sites, efficiently quenching halogen species and producing halogenated byproducts. , Nevertheless, Br-DBPs concentrations significantly decreased, but the TOBr levels elevated in the presence of NOM (Figure c, d). In contrast, bromine in THMs and HAAs accounts for more than 50% of TOBr in conventional halogenation processes .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…( OECD, 2013 ; Moon et al, 2021 ). As disinfectants to be evaluated, chlorine dioxide (ClO 2 ) and peracetic acid (PAA) were selected in consideration of food grade, persistence, and generation of toxic by-products such as trihalomethane ( Aieta and Berg, 1986 ; Farinelli et al, 2022 ). As ethanol (EtOH) is known to be effective in inactivating SARS-CoV-2 on various surface materials, food-grade ethanol was used in this study ( Jung et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%